2017
DOI: 10.1177/1010428317695017
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of ten-eleven translocation genes in endometrial cancers

Abstract: Ten-eleven translocation proteins are α-ketoglutarate-dependent dioxygenases involved in the conversion of 5-methylcytosines (5-mC) to 5-hydroxymethylcytosine (5-hmC), 5-formylcytosine, and 5-carboxylcytosine that play a significant role in DNA demethylation. Deregulation of TET genes expression and changes in the level of 5-hmC are thought to be associated with the onset and progression of several types of cancer, but there are no such data related to endometrial cancer. The aim of the work was to investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
36
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 41 publications
7
36
0
2
Order By: Relevance
“…These 5mC oxidation products were implicated as intermediates in the conversion of 5mC to unmodified cytosines. Levels of 5hmC have recently been positively correlated with the expression levels of the Tet enzyme family [50]. As shown in Figure 2(g) and in line with our observation that M1 activation is marked with a global increase in 5hmC levels, we found that expression levels of Tet 2 increased significantly during M1 activation.…”
Section: Global Changes In 5mc and 5hmc Levels During M1 Activation Asupporting
confidence: 89%
“…These 5mC oxidation products were implicated as intermediates in the conversion of 5mC to unmodified cytosines. Levels of 5hmC have recently been positively correlated with the expression levels of the Tet enzyme family [50]. As shown in Figure 2(g) and in line with our observation that M1 activation is marked with a global increase in 5hmC levels, we found that expression levels of Tet 2 increased significantly during M1 activation.…”
Section: Global Changes In 5mc and 5hmc Levels During M1 Activation Asupporting
confidence: 89%
“…A study of hepatocellular carcinoma observed decreased expression of TET1 , but not TET2 and TET3 [ 29 ]. Moreover, decreased TET1 expression correlates with tumor progression and may serve as a potential prognostic biomarker in endometrial cancer [ 30 ]. Similarly, loss of 5hmC in gastric cancer was mainly correlated with the downregulation of TET1 [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…DNA methylation and demethylation are dynamic processes mediated by the DNMT and TET family proteins, respectively. The most important function of TET1 (ten‐eleven translocation) protease activity is to convert 5‐methylcytosine (5‐mC) into 5‐hydroxymethylcytosine (5‐hmC), while the TET2 and TET3 mRNAs do not differ in GC . Tet1 expression was also significantly reduced in CagA + GC tissues compared with that in noncancerous tissues .…”
Section: Discussionmentioning
confidence: 99%
“…The most important function of TET1 (ten-eleven translocation) protease activity is to convert 5-methylcytosine (5-mC) into 5-hydroxymethylcytosine (5-hmC), while the TET2 and TET3 mRNAs do not differ in GC. 29,30,[45][46][47][48][49] Tet1 expression was also significantly reduced in CagA + GC tissues compared with that in noncancerous tissues. 18 According to many studies and experimental data, H pylori infection/CagA promotes the transport of the DNMT1 and DNMT3B proteins (DNA methyltransferase 3 B) into the nucleus of cells, and this may be related to the silencing of transcriptional expression, such as E-cadherin (CDH1) and forkhead box (Fox).…”
Section: T a B L E 2 Helicobacter Pylorimentioning
confidence: 91%